Two new species of Parosmylus Needham (Neuroptera, Osmylidae) from China, with a key to Chinese species - Wang, Yongjie; Liu, Zhiqi (Zootaxa, 2009)
Two new species of the genus Parosmylus are described: they are Parosmylus liupanshanensis sp. nov., Parosmylus brevicornis sp. nov. A key to species in China is given.